Unintentional weight loss in adults 65 years or older a symptom of physical and psychiatric etiologies - (:unkn) unknown (My University, 2022)
Unintentional weight loss is defined as a more than 5% decrease in body weight within 1 year. Various physical and psychiatric etiologies cause unintentional weight loss, including major depressive disorder (MDD). We present the case of a 69-year-old woman who lost 10 kg in 2 months. She had anhedonia, mobility limitations, and incontinence. Her Mini Nutritional Assessment score indicated malnutrition, whereas her Geriatric Depression Scale score indicated a diagnosis of MDD. Whole-body fluorodeoxyglucose (FDG)-positron emission tomography/computed tomography showed intensely increased FDG uptake in the muscles adjacent to the right and left mandibular rami and the temporal muscle, compatible with jaw clenching associated with the patient\"s MDD. Subsequent temporal muscle biopsy did not suggest the causes of malignant disorders, dermatomyositis, or polymyositis. Having ruled out all possible organic pathologies, the patient was thus diagnosed with MDD. Escitalopram was prescribed for her MDD, and oral nutritional supplement treatments were initiated for her malnutrition. Patients who present with unintentional weight loss should be assessed first for physical etiologies, and then psychiatric etiologies, particularly as weight loss may be a major symptom of MDD in older adults.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); Psikiyatri; CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PSYCHIATRY; Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Nöroloji (klinik); Yaşam Bilimleri; Psychiatric Mental Health; Psychiatry and Mental Health; Neurology (clinical); Life Sciences; FDG-PET; CT; major depressive disorder; older adults; unintentional weight loss; DEPRESSION; FDG-PET/CT; major depressive disorder; older adults; unintentional weight loss